Schistosomiasis transmission: A machine learning analysis reveals the importance of agrochemicals on snail abundance in Rwanda - Kagabo, Joseph; Tabo, Zadoki; Kalinda, Chester; Nyandwi, Elias; Rujeni, Nadine (Public Library of Science, 2024)
Background Schistosomiasis is an important snail-borne parasitic disease whose transmission is exacerbated by water resource management activities. In Rwanda, meeting the growing population's demand for food has led to wetlands reclamation for cultivation and increased agrochemical enrichment for crop production. However, the ecological consequences of agrochemical enrichment on schistosomiasis transmission remain unexplored. Methods A malacological survey was conducted in 71 villages selected from 15 schistosomiasis endemic districts. Snail sampling was done in wetlands used for agriculture, along lake Kivu and at constructed multipurpose water dams. Water physico-chemical parameters were collected at all snail sampling sites. Analysis of collected data was performed using Xgboost (gain) and Random Forest (mean decrease in accuracy), machine learning techniques, to construct models that evaluate and categorize the importance of all physico-chemical properties on the presence and abundance of intermediate host snails (IHS). Results Different sets of parameters were relevant for the presence and abundance of Biomphalaria spp. and/or Bulinus spp. snails. Electrical conductivity, elevation, magnesium and lead content were deemed to shape the presence and abundance of Bulinus spp. snails. The impact of phosphate ion concentration, ammonia ions, total nitrogen and total organic carbon levels mirrored their importance towards the presence and abundance of Biomphalaria spp. Factors such as pH, electric conductivity, total nitrogen content and total organic carbon influenced the coexistence of both species. Our study highlights the value of integrating a wide range of predictor variables, enabling effective variable selection to uncover important predictors of snail distribution. Conclusion The results suggest that agrochemical compounds can enhance the abundance of IHS leading to an increased risk of Schistosoma transmission. Snail surveillance could therefore be integrated into agricultural expansion projects in our match towards schistosomiasis elimination. Recognizing the impact of agrochemicals on IHS is crucial for minimizing schistosomiasis transmission among those working in wetlands while meeting the growing need for food.